Stability of Caputo fractional hyperbolic systems - Arfaoui, Hassen (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.95 We study the problems of well-posedness and stability for fractional linear hyperbolic systems (FLHS) with the Caputo time-fractional derivative. First, the existence and uniqueness are established for the global solution of the FLHS. Then we obtain some polynomial stability results for the FLHS in different Hilbert spaces. Finally, some numerical examples are presented to confirm the theoretical results.